The Key Roles of Makorin RING Finger Protein 3 (MKRN3) During the Development of Pubertal Initiation and Central Precocious Puberty (CPP) - Liu, Jiang; Li, Tangluo; Peng, Mindan; Luo, Min; Gui, Zihao; Long, Shuanglian; Mo, Zhongcheng; He, Weiguo (Current Molecular Medicine, 2023)
Puberty is initiated from the continuous and growing pulsatile secretion of gonadotropin-releasing hormone (GnRH) in the hypothalamus and then the activation of the hypothalamic-pituitary-gonadal (HPG) axis. Numerous factors involve pubertal initiation, whose abnormality may come from the dysfunction of these regulators. Makorin RING finger protein 3 (MKRN3) inhibits the secretion of GnRH and plays indispensable roles during the development of pubertal onset, and mutations of MKRN3 showed the commonest genetic cause of central precocious puberty (CPP). Recently, growing studies have revealed the functional mechanisms of MKRN3 in the pubertal initiation and the occurrence of CPP. In this review, we mainly summarized the research advances on the roles of MKRN3 in the development of pubertal onset and their underpinning mechanisms, contributing to a better understanding of the precise mechanisms of pubertal initiation and the pathogenesis of CPP.
Keywords: CPP